Pemanfaatan Listrik Tenaga Surya Sebagai Pasokan Listrik Untuk Menghidupkan Mesin Pompa Air Masyarakat Dusun Cilatak, Desa Sukadana, Kecamatan Ciomas, Kabupaten Serang, Banten - Sari, Dewi Purnama; Kurniasih, Novi; Fernandes, Alex (TERANG, 2020)
The Community Service program activity of the Electricity and Renewable Energy Faculty lecturer team at the PLN Technology Institute for the 2019/2020 fiscal year was carried out in Sukadana village, Ciomas district, Serang region, Banten precisely at RT 011 RW 003 Cilatak hamlet. The selection of Sukadana village as a place to implement Community Service is because this village is still experiencing problems in the construction and development facilities and infrastructure. The problems that are currently being experienced by villagers regarding the clean water distribution for ablution of villagers in the mosque. During this time for ablution in mosque, villagers only rely on water from mountain springs whose distribution relies on gravitational pressure through a plastic hose and accommodated in a large tub located beside the mosque. In addition to being used for ablution, water is also used by villagers to bathing, washing, etc., so that when used for ablution sometimes it is no longer clean because it has been mixed with soapy water used for bathing and washing. Based on those problems, our team provided solution to partner in the form of infrastructure development and clean water supply by reconfiguring the clean water distribution installation for ablution in the mosque by installing solar water pump. The method used in the implementation of this Community Service activity is to approach the villagers during the survey through interviews by providing solution to the problem and conducting questionnaires and socialization in the form of a brief education. The results of the activities have been done by installing 2 units of DC water pump @180 Watt, 4 units of polycrystalline solar modules @100 Wp, 2 units of battery @100 Ah 12 V and 2 units of solar charge controller. With the implementation of Community Service activities in Sukadana village, aside from being able to help overcome the problems faced by partner, besides that it can provide progress and development of infrastructure for partner village and the existence of a partnership that makes that village as IT PLN assisted village.